PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKANHASIL BELAJAR IPA SISWA KELAS IVASD NEGERI 62 PEKANBARU - Saswita, Gusneli; Marhadi, Hendri; Alexander, Jessi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :This research aims to improve grade IV student’s natural science learning achievement at SDN 62 Pekanbaru academic year 2014/ 2015 through “ Application of the model Contextual Teaching And Learning (CTL)”. Setting of the problem is “ is the application of the model Contextual Teaching And Learning (CTL) can improve grade IV student’s natural science learning achievement at SDN 62 Pekanbaru”. This research was conducted in March. The number of students are 30 students which contain of 14 boys and 16 girls. This research is classroom action research which contains of two cycles. Each cycles consist of 2 meeting. Parameter of the research is involved students learning achievement after the action in each cycles (daily test I, II,). Instrument of the research contains of learning tools (syllabus, RPP, LKS, learning result paper sheet). Observation of student and teacher activity sheet. Data of the research will analyze descriptively. Research data show that learning achievement has increased.Where prior to the application of the model Contextual Teaching and Learning (CTL) as much as any 9 students (30%)scored daily test is above or equal to the minimum completeness criteria (KKM). It was improved to 67 after using the application of the model Contextual Teaching and learning in first cycle. In the second cycle increased 81,1. Activities of the student during the learning process (I, II cycles) is can be categorized very well by an average 87,5%. From the explanation above shows that application of the model Contextual Teaching and learning can be improving grade IV students natural science learning achievement at SDN 62 Pekanbaru.Keyword : the model Contextual Teaching and learning, natural science achievement